PEMBINAAN NARAPIDANA ANAK DI LEMBAGA PEMBINAAN KHUSUS ANAK KELAS 1A KUPANG - Samara, Finsensius; Ursula Idam Putri, Frederika Bernadeta; Alfiayu Zigha Nanga, Antonia (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
In LPKA, children who have received legal decisions receive educational, rehabilitative, and productive guidance so that they can reintegrate with the community. The goal is to see that the coaching of Child Prisoners at the Kupang Class 1a Special Children's Development Institution has been carried out in accordance with the rules in the law. The type of research used is the Empirical research method. Empirical research is based on reality in the field or through direct observation. The location of the research is at the Special Children's Development Institution (LPKA) Class 1A Kupang, this research is intended for residents of LPKA Class 1A Kupang. There are 40 child inmates in LPKA Class 1A Kupang in 2023. The programs run by LPKA Class 1A Kupang City are, Faith Development and Personality, Education, and Physical Development. Various kinds of obstacles faced in the implementation of coaching include, namely, the main obstacle is the lack of a clear legal basis or implementation guidelines to support special coaching for children and related to students in LPKA Class 1A Kupang often come from different backgrounds. This condition shapes their character which lowers their motivation to participate in coaching programs. LPKA Class 1A Kupang runs an integrated coaching program for students with the aim of rehabilitation and social reintegration. Government Recommendations need to develop implementing regulations or more specific guidelines related to coaching in LPKA and implement the Right Transfer Mechanism for Adult Students.